Konsep Reward dan Punishment dalam Hadist Tarbawi Serta Relevansinya Terhadap Pendidikan Kontemporer - Luthfia Hanifatus Saiyidah; Linggaria Lova; A.Gani; Muhammad Akmansyah; Amiruddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
The concepts of reward and punishment are understood as educational strategies aimed at shaping students’ behavior and character. In the tradition of Islamic education, these principles are recognized through the concepts of targhīb (reward) and tarhīb (punishment), which are rooted in the hadiths of the Prophet Muhammad SAW. This article is designed to analyze the concepts of reward and punishment in hadith tarbawi by referring to three primary hadiths, while also examining their relevance to contemporary educational practices. A qualitative approach was employed in this study using a library research method. The findings indicate that reward in the hadith tradition emphasizes spiritual and moral dimensions, whereas punishment is implemented gradually, proportionally, and based on the principle of gentleness. These concepts are considered relevant to reinforcement theory in modern educational psychology; however, within the hadith perspective, they encompass broader ethical and transcendental dimensions. Therefore, the integration of hadith tarbawi values is viewed as capable of strengthening humanistic educational practices oriented toward character development.